2020
DOI: 10.1186/s41824-020-00082-y
|View full text |Cite
|
Sign up to set email alerts
|

A twisted tale-radiological imaging features of COVID-19 on 18F-FDG PET/CT

Abstract: The COVID-19 pandemic has had a major impact on health care systems across the globe in a short period of time. There is a growing body of evidence surrounding the findings on hybrid imaging with FDG-PET/CT, and this case highlights the importance of molecular imaging in better understanding of the biomarkers of the disease which ultimately determine the success in building a model to predict the disease severity and monitoring the response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In clinical studies of COVID-19, lymph node enlargement has been considered an indicator of the infection severity and was used to indicate a worse prognosis [ 57 , 58 ]. In another case report, researchers have proposed that higher SUVmax values of lymph nodes could herald a more severe condition of the SARS-CoV-2 infection, which further underscore the role of lymphadenopathy as a predictor of a worse outcome [ 59 ]. In addition, some studies reported that the lesions of mediastinal lymph nodes with high metabolism did not spatially match the distribution of the pulmonary inflammation, suggesting that the glucose uptake in lymph node might be an independent imaging marker of COVID-19 [ 59 , 60 ].…”
Section: Pet In the Prognosis Evaluation Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical studies of COVID-19, lymph node enlargement has been considered an indicator of the infection severity and was used to indicate a worse prognosis [ 57 , 58 ]. In another case report, researchers have proposed that higher SUVmax values of lymph nodes could herald a more severe condition of the SARS-CoV-2 infection, which further underscore the role of lymphadenopathy as a predictor of a worse outcome [ 59 ]. In addition, some studies reported that the lesions of mediastinal lymph nodes with high metabolism did not spatially match the distribution of the pulmonary inflammation, suggesting that the glucose uptake in lymph node might be an independent imaging marker of COVID-19 [ 59 , 60 ].…”
Section: Pet In the Prognosis Evaluation Of Covid-19mentioning
confidence: 99%
“…In another case report, researchers have proposed that higher SUVmax values of lymph nodes could herald a more severe condition of the SARS-CoV-2 infection, which further underscore the role of lymphadenopathy as a predictor of a worse outcome [ 59 ]. In addition, some studies reported that the lesions of mediastinal lymph nodes with high metabolism did not spatially match the distribution of the pulmonary inflammation, suggesting that the glucose uptake in lymph node might be an independent imaging marker of COVID-19 [ 59 , 60 ]. However, considering the limited number of studies as well as the small sample size, further studies are essential to explore the potential role of hypermetabolism in lymph nodes detected by PET in the management of COVID-19.…”
Section: Pet In the Prognosis Evaluation Of Covid-19mentioning
confidence: 99%
“…During the recent pandemic, several papers have reported on the [ 18 F]-fluorodeoxyglucose positron-emission tomography ( 18 FDG PET) findings in coronavirus disease-19 . Increased FDG uptake is usually seen at the site of lung abnormalities shown on computed tomography (CT) and may also be present in mediastinal lymph nodes (O'Neill et al 2020;Polverari et al 2020). This is not unexpected since 18 FDG avidity is typical of inflammatory/infectious diseases, and some authors have proposed 18 FDG PET as a non-invasive biomarker for monitoring viral infections (Brust et al 2006;Chacko et al 2017).…”
mentioning
confidence: 99%